Conversion of Glycerol to Ethanol by Integrating Ultrasonic and Ni/ZSM-5 Catalyst - Devi Indrasari Mustopa Putri; Sumari Sumari; Handoko Darmokoesomo; Ganden Supriyanto; Nur Arief Nugroho (Eksergi, 2023)
The increased production of biodiesel which is used as an alternative fuel has led to an increase in the by-product in the form of glycerol. This glycerol byproduct can be utilized by converting it into other compounds such as ethanol. The production of ethanol from glycerol requires a catalyst that can break down the molecular size of glycerol, one of which is zeolite. One type of zeolite that is good to use is ZSM-5, because this type of zeolite has a high degree of thermal stability, acid stability and selectivity. The catalytic properties of ZSM-5 can be improved by impregnating metals from the transition group, in this study using Ni (nickel). The results obtained that the catalyst Ni/ZSM-5 has a total acidity value of 0.920 mmol/g and has a specific surface area of 138.754 m2/g. The highest ethanol product was produced at 4 hours of sonication, which was 20.362%.